Amino acids in animal nutrition - D'Mello, J. P. Felix (CABI, 2003)
Amino acid metabolism and nutrition of farm animals continues to be an active area of research. Fully updated, this second edition discusses the nutrition of a wider range of species, including companion animals. There are species-specific chapters on pgs, poultry, ruminants and companion animals